Association between mutational subgroups, Warburg‐subtypes, and survival in patients with colorectal cancer. (3rd July 2022) - Offermans, Kelly; Jenniskens, Josien C. A.; Simons, Colinda C. J. M.; Samarska, Iryna; Fazzi, Gregorio E.; van der Meer, Jaleesa R. M.; Smits, Kim M.; Schouten, Leo J.; Weijenberg, Matty P.; Grabsch, Heike I.; van den Brandt, Piet A.
Abstract: Background: Previous research suggests that Warburg‐subtypes are related to potentially important survival differences in colorectal cancer (CRC) patients. In the present study, we investigated whether mutational subgroups based on somatic mutations in RAS, BRAF, PIK3CA, and MET, which are known to promote the Warburg‐effect, as well as mismatch repair (MMR) status, hold prognostic value in CRC. In addition, we investigated whether Warburg‐subtypes provide additional prognostic information, independent of known prognostic factors like TNM stage. Methods: CRC patients ( n  = 2344) from the prospective Netherlands Cohort Study (NLCS) were classified into eight mutually exclusive mutational subgroups, based on observed mutations in RAS, BRAF, PIK3CA, and MET, and MMR status: All‐wild‐type + MMRproficient, KRAS mut  + MMRproficient, KRAS mut  +  PIK3CA mut  + MMRproficient, PIK3CA mut  + MMRproficient, BRAF mut  + MMRproficient, BRAF mut  + MMRdeficient, other + MMRproficient, and other + MMRdeficient . Kaplan–Meier curves and Cox regression models were used to investigate associations between mutational subgroups and survival, as well as associations between our previously established Warburg‐subtypes and survival within these mutational subgroups. Results: Compared to patients with all‐wild‐type + MMRproficient CRC, patients with KRAS mut  + MMRproficient, KRAS mut  +  PIK3CA mut  + MMRproficient, BRAF mut  + MMRproficient, or other + MMRproficient CRC had a statistically significant worse survival (HRCRC‐specific ranged from 1.29 to 1.88). In contrast, patients with other + MMRdeficient CRC had the most favorable survival (HRCRC‐specific 0.48). No statistically significant survival differences were observed for the Warburg‐subtypes within mutational subgroups. Conclusion: Our results highlight the prognostic potential of mutational subgroups in CRC. Warburg‐subtypes did not provide additional prognostic information within these mutational subgroups. Future larger‐scale prospective studies are necessary to validate our findings and to examine the potential clinical utility of CRC subtyping based on mutational subgroups. Abstract : In this large, population‐based series of CRC patients, we have shown that mutational subgroups, based on the observed mutation frequencies of RAS ( KRAS, NRAS, HRAS ), BRAF, PIK3CA, and MET, as well as patients' MMR status, are associated with important differences in survival. Warburg‐subtypes did not provide additional prognostic information within these mutational subgroups.